2003
DOI: 10.2337/diabetes.52.10.2526
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylureas Rapidly Cross Phospholipid Bilayer Membranes by a Free-Diffusion Mechanism

Abstract: Because sulfonylureas directly activate the exocytotic machinery, we were interested in the extent to which these compounds penetrate the ␤-cell plasma membrane and the underlying molecular mechanism(s). We now provide evidence that sulfonylureas cross phospholipid bilayer membranes rapidly and effectively by a free-diffusion mechanism. Two sulfonylurea compounds investigated by 1 H nuclear magnetic resonance spectroscopy, glibenclamide and tolbutamide, were found to incorporate into phospholipid bilayers, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…At variance with first-generation sulfonylureas, the compounds also generate a secretory activity after their removal from the extracellular medium (22). This sustained effect coincides with cellular accumulation of the drug, primarily in membranes of secretory vesicles and mitochondria (22)(23)(24)(25). It has been attributed to a protein kinase C activation following glibenclamide stimulation of diacylglycerol synthesis (21,26).…”
Section: Discussionmentioning
confidence: 99%
“…At variance with first-generation sulfonylureas, the compounds also generate a secretory activity after their removal from the extracellular medium (22). This sustained effect coincides with cellular accumulation of the drug, primarily in membranes of secretory vesicles and mitochondria (22)(23)(24)(25). It has been attributed to a protein kinase C activation following glibenclamide stimulation of diacylglycerol synthesis (21,26).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of sulphonylureas to the sulphonylurea receptor (SUR)1 subunit of these channels results in closure of the Kir6.2 pore, which in turn evokes membrane depolarisation, influx of extracellular calcium and, ultimately, exocytosis of insulin (Ashcroft & Gribble 1999, Bryan et al 2005. In addition to this mechanism, several studies have reported direct intracellular effects of sulphonylureas upon exocytosis independent of K ATP -channel function (Flatt et al 1994, Eliasson et al 1996, Tian et al 1998, Ball et al 2000a, Kamp et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they were able to detect diazoxide in the cerebrospinal fluid of rodents after oral ingestion reaching levels of 0.26 6 0.06 mg/mL 1 h after gavage and 0.78 6 0.03 mg/mL by 4 h, providing convincing evidence that diazoxide penetrates the blood-brain barrier (BBB) (35). Species differences may affect BBB permeability to diazoxide; however, diazoxide contains an ionizable sulfonyl group that makes it extremely lipid soluble and therefore able to partition into the lipid bilayer for penetration through the BBB (36). These studies support the hypothesis that diazoxide acts to amplify the CRR to acute hypoglycemia through a direct action in the brain.…”
Section: Discussionmentioning
confidence: 99%